2018
DOI: 10.1109/tnsre.2017.2771383
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Inertial Sensors for Fall Risk Assessment and Prediction in Older Adults: A Systematic Review and Meta-Analysis

Abstract: Wearable inertial sensors have been widely investigated for fall risk assessment and prediction in older adults. However, heterogeneity in published studies in terms of sensor location, task assessed and features extracted is high, making challenging evidence-based design of new studies and/or real-life applications. We conducted a systematic review and meta-analysis to appraise the best available evidence in the field. Namely, we applied established statistical methods for the analysis of categorical data to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
122
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(127 citation statements)
references
References 31 publications
2
122
0
3
Order By: Relevance
“…Medical devices effectiveness is dependent upon several factors including the environment in which are utilised (e.g., sterilised or not, temperature, humidity, dust), the experience of the operators, maintaining, servicing and preparing the medical device 9 . For instance, recent studies demonstrated that even the positioning of applied parts (e.g., probes, sensors) in a trial might affect the significance of the results 10 . Therefore, pursuing a precision medicine approach in trialling deep learning (DL)-based medical technologies requires particular attention in the way the study is designed, executed and its results analysed [11][12][13] .…”
mentioning
confidence: 99%
“…Medical devices effectiveness is dependent upon several factors including the environment in which are utilised (e.g., sterilised or not, temperature, humidity, dust), the experience of the operators, maintaining, servicing and preparing the medical device 9 . For instance, recent studies demonstrated that even the positioning of applied parts (e.g., probes, sensors) in a trial might affect the significance of the results 10 . Therefore, pursuing a precision medicine approach in trialling deep learning (DL)-based medical technologies requires particular attention in the way the study is designed, executed and its results analysed [11][12][13] .…”
mentioning
confidence: 99%
“…In this study, we incorporated sensors while using logistic regression as an analytical method for prediction of multiple assessment tools, also simulating experts to verify the availability of sensors. Data collection among the elderly can be very difficult [5,56], so it is not easy to strike a balance with gender restrictions. Therefore, this study discussed the judgment of falls; any discussion of gender differences was necessarily rather limited.…”
Section: Discussionmentioning
confidence: 99%
“…These clinical assessments provide an overview of the fall-risk snapshots but are usually subjective, and those who use threshold assessment scores for performing the classification are considered to be decreasing rather than increasing [4]. Therefore, previous relevant studies have used the timed up and go (TUG) time score as a clinical evaluation item to overcome the subjective interpretation of falls [5]. The objective of clinical screenings is to find the outliers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most WWD studies Activity studies Affect studies Figure 7: Comparison between modeling techniques used for either affect or activity recognition. [38][39][40][41]45], activity tracking [43], and home monitoring [15,49], and there is a lack of studies related to education [46], security [47], and child care.…”
Section: Discussionmentioning
confidence: 99%